Monogenea (van Beneden, 1858) Carus, 1863 de peces marinos del litoral mexicano del Golfo de México y del Mar Caribe. V - Caballero y C., Eduardo (Universidad de Costa Rica, 1972)
A new genus, Paramicrocotyle and two new species, P. atriobursata and P. tampicensis, of the family Microcotylidae Taschenberg are described; 16 species formerly placed in the genus Microcotyle van Beneden and Hesse, 1863 are referred to the new genus.The differential characters of the new genus are: structure of the prohaptor and opisthohaptor; structure and shape of the genital atrium; and tbe prcsence of two vitellovaginal pouches.The species Paramicrocotyle tampicensis differs from P. atriobursata fundamentally in the shape and structure of the genital atrium, the prohaptor, and the opisthohaptor, as well as in the form of the male and female reproductive complexes. It resembles Paramicrocotyle archosargi (MacCallum, 1913) n. combo in the shape and structure of the posterior portion of the genital atrium, but differs in those of the anterior portion. Similarly, the genital atrium and other structures distinguish it from the other species of Paramicrocotyle le n. g. The vitellovaginal pouches are well developed and full of spermatozoa in P. tampicensis.